2017
DOI: 10.1007/s12264-017-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Defects in Spine Formation or Pruning in Two Gene Duplication Mouse Models of Autism

Abstract: Autism spectrum disorder (ASD) encompasses a complex set of developmental neurological disorders, characterized by deficits in social communication and excessive repetitive behaviors. In recent years, ASD is increasingly being considered as a disease of the synapse. One main type of genetic aberration leading to ASD is gene duplication, and several mouse models have been generated mimicking these mutations. Here, we studied the effects of MECP2 duplication and human chromosome 15q11-13 duplication on synaptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 65 publications
0
28
1
5
Order By: Relevance
“…Interestingly, defective synaptic refinement and dysfunctional microglia are associated with ASD (Kim et al, 2017;Tang et al, 2014;Wang et al, 2017).…”
Section: Autophagy and The Functional Role Of Trem2-dap12 In Develomentioning
confidence: 99%
“…Interestingly, defective synaptic refinement and dysfunctional microglia are associated with ASD (Kim et al, 2017;Tang et al, 2014;Wang et al, 2017).…”
Section: Autophagy and The Functional Role Of Trem2-dap12 In Develomentioning
confidence: 99%
“…Una línea de investigación fecunda dentro de esta perspectiva refiere al estudio de los métodos, por medio de los cuales los distintos investigadores logran realizar un análisis minucioso y certero de los procesos neuronales y genéticos del autismo. Es importante destacar aquí que, aunque las técnicas de neuroimagen del cerebro humano han identificado regiones y circuitos implicados en los trastornos, numerosos autores coinciden en optar por el estudio de modelos de patologías o síndromes en animales, más específicamente, de ratones (Xu, Miller y Pozzo-Miller, 2014;Lombardi, Baker y Zoghbi, 2015;Hulbert y Jiang, 2016;Sztainberg y Zoghbi, 2016;Fuccillo, 2016;Wang et al, 2017).…”
Section: La Perspectiva Genéticaunclassified
“…En otro artículo de aparición reciente, Wang et al (2017) proponen estudiar los efectos de la duplicación del gen MECP2 y la duplicación del cromosoma humano 15q11-13 sobre el desarrollo sináptico y el cableado del circuito neural en las cortezas sensoriales del ratón. Los autores tomaron como punto de partida dos cuestiones: por un lado, que los ratones que llevan la duplicación del gen MECP2 tenían defectos específicos en la poda de la columna vertebral; por otro lado, que la duplicación del 15q11-13 había deteriorado la formación de la columna vertebral de los ratones.…”
Section: La Perspectiva Genéticaunclassified
See 1 more Smart Citation
“…A number of mouse models of syndromic ASD display social impairment and repetitive behavior, the core features of ASD, although they vary widely in additional co-morbidities, and in alternations in excitatory and inhibitory synaptic transmission in various neuronal circuits. In investigating synaptic alterations in ASD mouse models, Wang et al [45] examined spine density changes in two relatively well-characterized mouse gene-duplication models of ASD, namely the MECP2 duplication and human chromosome 15q11-13 duplication models. They found that, in the mouse primary somatosensory cortex, 15q11-13 duplication mostly affects spine formation at 1 month of postnatal development, while MECP2 duplication interferes with spine pruning at 3 months, without significantly affecting spine formation.…”
mentioning
confidence: 99%